Improving Al-Qur’an Recitation Through Multimedia Content Production at SMPN 5 Palangga Gowa - Wirawan, Agung; Syahid, Akhmad; Azhar, Muh; Mustamin, Mustamin; Wahab, Abdul (Jurnal Kajian dan Pengembangan Umat, 2025)
This study examines how creating multimedia content production can help ninth grade students read the Qur'an more effectively. Students of SMPN 5 Pallangga, Gowa Regency. Analyzing the efficacy of learning strategies that combine text, audio, visual, and video media is the main objective of this study. The Classroom Action Research (CAR) approach, used in this study, was carried out in two cycles: planning, implementation, observation, and reflection. All research participants were ninth grade students. A. After the implementation of multimedia-based learning, the research findings showed a significant increase in the quality of students' Qur'an reading. Before the intervention, 28.94% of students met the completion criteria; in the first cycle, the figure increased to 60.52%, and in the second cycle, it increased to 89.47%. Students showed improvements in self-confidence, tenacity, and willingness to learn in addition to improving their proficiency in reading the Qur'an. These results indicate that creating multimedia content can be a useful tactic in teaching Islamic Religious Education, especially in terms of improving the standard of Qur'an reading. It is recommended that educators use this approach consistently to optimize learning outcomes, foster an engaging learning environment, and help students develop their attitudes and personalities. In addition to making learning materials easier to understand and more engaging, this method fosters a learning environment that helps students' attitudes and character development in religious education.